Seismic characterization of fluid migration and Pockmarks formation in the Estremadura Spur, Western Iberian Margin - Duarte, D. (2016)
: A field with more than 30 pockmarks was recently discovered in the Estremadura Spur outer shelf (Lourinhã Monocline). The processing of high-resolution seismic lines permitted the characterization of this pockmark field and of the seismic sequence of the Plio-Quaternary basin where they occur. Results show that this region has been affected by several episodes of fluid migration and fluid escape during the Plio-Quaternary, expressed by the presence of the pockmarks that at the present-time seem to be mainly inactive.